Analysis on the Factors Influencing Frost Resistance of Cement-stabilized Soil - LI Xuede; LIN Qingmei; PENG Xuhua; SU Yeping; ZHAO Yangjun (Renmin Zhujiang)
The frost resistance is an important index to evaluate the durability of stabilized soil structure,this paper analyzes the effects of soil moisture content and cement content on frost resistance of cement-stabilized soil.The results show that:the cement content has a significant influence on the frost resistance of cement-stabilized soil,and the frost resistance increases with increasing cement content;the soil moisture content has little effect on the frost resistance of cement-stabilized soil,and the frost resistance is the best with nearly optimum soil moisture content,which can provide basic parameters for improving the frost resistance of cement-stabilized soil.